Kondisi gigi yang masih lengkap mempengaruhi kualitas hidup manula di Kota Makassar (Condition of complete dentition affects the quality of life of the elderly in Makassar ) - Prastuti Wulandari Kosasih; Eri H. Jubhari (Journal of Dentomaxillofacial Science, 2014)
Aging is a natural process which causes physical, psychological, and social deteriorations, so it can cause problems tothe elderly, especially health problems in Makassar. The local office of Health Department in Makassar determined theoptimum degree of health in accordance with result of indicators of Healthy Indonesia 2010 which were indicated bythe dental and oral health as an element of the quality of life. This research aims to observe the effect of completedentition on the quality of life of the elderly in Makassar. With the observational analytic study using a cross-sectionaldesign, the sample were chosen from the elderly who inhabit and settle in Makassar, South Sulawesi, above 60 yearsold and hadâ‰¥ 20 teeth. The primary data were collected using OHIP-14 questionnaire. The results of simple linearregression test using SPSS version 22 indicate that the elderly with complete dentition have a significance level of0.003 which is smaller compared with the significance criteria (0.05). It was concluded that the condition of completedentition affect the quality of life of the elderly in Makassar.